Manejo da irrigação com água salina na cultura do amendoim em solo com e sem cobertura morta vegetal nas fases fenológicas - Sousa, Henderson Castelo (2022)
Irrigation is a technique that guarantees an increase in agricultural production, however, semi-arid regions such as the Brazilian Northeast are characterized by having lower quality water as an alternative water source for this purpose. Peanut cultivation in these regions is compromised due to the accumulation of salts present in the irrigation water, affecting the chemical attributes of the soil and productivity, requiring the use of conservation practices that attenuate these effects. In this sense, mulch appears as a strategy to mitigate saline stress. Thus, the objective was to evaluate the effect of irrigation with saline water under different strategies of use of mulch in peanut cultivation. The experiment was carried out at the Experimental Farm Piroás, from the Universidade Internacional da Lusofonia Afro-Brasileira, Redenção, Ceará, in a randomized block design, using a split-plot scheme, in which the plots corresponded to two electrical conductivities of the irrigation water (ECw: supply water - 0.8 dS m-1 and saline solution of 4.0 dS m-1 ), and the subplots to six strategies of insertion of vegetal mulch based on the phenology of the crop (ME1: mulch throughout the cycle; ME2: flowering phase - 25 DAS; ME3: gynophore appearance - 36 DAS; ME4: pod formation - 47 DAS; ME5: final flowering phase - 65 DAS; ME6: no mulch), with five replications. At the end of the cycle, the following variables were evaluated: number of commercial pods; number of non-commercial pods; number of grains per pod; pod length and diameter; pod mass; mass of 100 grains; productivity and water use efficiency. The chemical attributes of the soil were also evaluated: contents of P, K, Na, Ca, Mg and the electrical conductivity of the saturation extract and soil pH, percentage of exchangeable sodium and soil organic matter. Irrigation with water of 4 dS m-1 negatively affects the chemical attributes of the soil, but provides a higher content of OM. The mulch insertion strategies mitigate saline stress favoring the reduction of Na, PST and ECes. ME1 increases soil potassium content under irrigation with lower salinity water. Irrigation with water of lower salinity (0.8 dS m-1 ) associated with the use of mulch throughout the peanut crop cycle provides greater performance in productivity and water use efficiency. Salt stress negatively affects production parameters and water use efficiency of peanut crops with and without the use of mulch in the phenological stages.